Clinical and Angiographic Outcomes of the First Korean-made Sirolimus-Eluting Coronary Stent with Abluminal Bioresorbable Polymer - Yang, Hyoung-Mo; Seo, Kyoung-Woo; Yoon, Junghan; Kim, Hyo-Soo; Chang, Kiyuk; Lim, Hong-Seok; Choi, Byoung-Joo; Choi, So-Yeon; Yoon, Myeong-Ho; Lee, Seung-Hwan; Ahn, Sung Gyun; Youn, Young Jin; et al. (Korean circulation journal, 2017)
This trial evaluated the safety and efficacy of the Genoss drug-eluting coronary stent. This study was a prospective, multicenter, randomized trial with a 1:1 ratio of Genoss drug-eluting stent (DES)™ and Promus Element™. Inclusion criteria were the presence of stable angina, unstable angina, or silent ischemia. Angiographic inclusion criteria were de novo coronary stenotic lesion with diameter stenosis >50%, reference vessel diameter of 2.5-4.0 mm, and lesion length ≤40 mm. The primary endpoint was in-stent late lumen loss at 9-month quantitative coronary angiography follow-up. Secondary endpoints were in-segment late lumen loss, binary restenosis rate, death, myocardial infarction (MI), target lesion revascularization (TLR), target vessel revascularization (TVR), and stent thrombosis during 9 months of follow-up. We enrolled 38 patients for the Genoss DES™ group and 39 patients for the Promus Element™ group. In-stent late lumen loss at 9 months was not significantly different between the 2 groups (0.11±0.25 vs. 0.16±0.43 mm, p=0.567). There was no MI or stent thrombosis in either group. The rates of death (2.6% vs. 0%, p=0.494), TLR (2.6% vs. 2.6%, p=1.000), and TVR (7.9% vs. 2.6%, p=0.358) at 9 months were not significantly different. This first-in-patient study of the Genoss DES™ stent showed excellent angiographic outcomes for in-stent late lumen loss and major adverse cardiac events over a 9-month follow-up.